2022
DOI: 10.1038/s41467-022-28696-9
|View full text |Cite
|
Sign up to set email alerts
|

Sequential metamaterials with alternating Poisson’s ratios

Abstract: Mechanical metamaterials have been designed to achieve custom Poisson’s ratios via the deformation of their microarchitecture. These designs, however, have yet to achieve the capability of exhibiting Poisson’s ratios that alternate by design both temporally and spatially according to deformation. This capability would enable dynamic shape-morphing applications including smart materials that process mechanical information according to multiple time-ordered output signals without requiring active control or powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 63 publications
(54 reference statements)
0
26
0
Order By: Relevance
“…Mechanical metamaterials are a class of artificial materials with unconventional mechanical properties, such as negative Poisson’s ratio [ 91 ], negative swelling ratio [ 92 ], energy absorption [ 93 ], reconfigurable deployment [ 94 ], and a tunable phononic response [ 95 ]. These extraordinary functionalities are not directly related to the intrinsic properties of their constituent materials, but are dependent upon the elaborately designed microstructures as the basic building blocks.…”
Section: Structural Instabilitymentioning
confidence: 99%
“…Mechanical metamaterials are a class of artificial materials with unconventional mechanical properties, such as negative Poisson’s ratio [ 91 ], negative swelling ratio [ 92 ], energy absorption [ 93 ], reconfigurable deployment [ 94 ], and a tunable phononic response [ 95 ]. These extraordinary functionalities are not directly related to the intrinsic properties of their constituent materials, but are dependent upon the elaborately designed microstructures as the basic building blocks.…”
Section: Structural Instabilitymentioning
confidence: 99%
“…[6,7,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Unfortunately, despite the large literature on auxetic mechanical metamaterials, very few papers report mechanical phase transitions. [57][58][59] In chemistry, thermodynamics, and generally physical sciences, phase transitions are the physical processes of transition between states corresponding to different properties. [60] They typically correspond to a change in the order of parameter that is defined depending on the investigated phenomenon and system.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in phasetransforming structures with magnetic inclusions, [58] it was shown that the resulting metamaterial can exhibit different static and dynamic mechanical properties, before and after being subjected to the external stimulus. Furthermore, in the case of nonmagnetic mechanical metamaterials, Farzaneh et al [57] studied sequential metamaterials with alternating Poisson's ratios under both compressive and tensile loads. Other examples include the work by Janbaz et al [59] where a strain-induced phase transition of Poisson's ratio was observed for a system consisting of a combination of stiff and soft bi-beams.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations